Associations between COVID-19 risk perceptions and mental health, wellbeing, and risk behaviours. Issue 11 (2nd December 2022) - Dyer, Maddy L.; Sallis, Hannah M.; Khouja, Jasmine N.; Dryhurst, Sarah; Munafò, Marcus R.
Abstract: Mental health has worsened, and substance use has increased for some people during the coronavirus (COVID-19) pandemic. Some cross-sectional studies suggest that higher COVID-19 risk perceptions are related to poorer mental health and greater risk behaviours (e.g. substance use). However, longitudinal and genetic data are needed to help to reduce the likelihood of reverse causality. We used cross-sectional, longitudinal, and polygenic risk score (PRS; for anxiety, depression, wellbeing) data from the Avon Longitudinal Study of Parents and Children (ALSPAC). We examined cross-sectional and prospective longitudinal associations between COVID-19 risk perceptions (i.e. cognitive, affective, self, other, and a combined 'holistic' measure) and mental health (i.e. anxiety, depression), wellbeing, and risk behaviours. Pandemic (April–July 2020) and pre-pandemic (2003–2017) data (ns = 233–5, 115) were included. Higher COVID-19 risk perceptions (holistic) were associated with anxiety (OR 2.78, 95% confidence interval [CI] 2.20 to 3.52), depression (OR 1.65, 95% CI 1.24 to 2.18), low wellbeing (OR 1.76, 95% CI 1.45 to 2.13), and increased alcohol use (OR 1.46, 95% CI 1.24 to 1.72). Higher COVID-19 risk perceptions were also associated with self-isolating given a suspected COVID-19 infection (OR 1.74, 95% CI 1.13 to 2.68), and less face-to-face contact (OR 0.83, 95% CI 0.70 to 0.98) and physical contact (OR 0.83, 95% CI 0.68 to 1.00). Pre-pandemic anxiety (OR 1.64, 95% CI 1.29 to 2.09) and low wellbeing (OR 1.41, 95% CI 1.15 to 1.74) were associated with higher COVID-19 risk perceptions. The depression PRS ( b 0.21, 95% CI 0.02 to 0.40) and wellbeing PRS ( b  − 0.29, 95% CI −0.48 to −0.09) were associated with higher and lower COVID-19 risk perceptions, respectively. Poorer mental health and wellbeing are associated with higher COVID-19 risk perceptions, and longitudinal and genetic data suggest that they may play a causal role in COVID-19 risk perceptions.